NOD2 Contributes to Porphyromonas gingivalis–induced Bone Resorption. (November 2014) - Prates, T.P.; Taira, T.M.; Holanda, M.C.; Bignardi, L.A.; Salvador, S.L.; Zamboni, D.S.; Cunha, F.Q.; Fukada, S.Y.
The NOD-like receptors are cytoplasmic proteins that sense microbial by-products released by invasive bacteria. Although NOD1 and NOD2 are functionally expressed in cells from oral tissues and play a role triggering immune responses, the role of NOD2 receptor in the bone resorption and in the modulation of osteoclastogenesis is still unclear. We show that in an experimental model of periodontitis with Porphyromonas gingivalis W83, NOD2 -/- mice showed lower bone resorption when compared to wild type. Quantitative polymerase chain reaction analysis revealed that wild-type infected mice showed an elevated RANKL/OPG ratio when compared to NOD2 -/- infected mice. Moreover, the expression of 2 osteoclast activity markers—cathepsin K and matrix metalloproteinase 9—was significantly lower in gingival tissue from NOD2 -/- infected mice compared to WT infected ones. The in vitro study reported an increase in the expression of the NOD2 receptor 24 hr after stimulation of hematopoietic bone marrow cells with M-CSF and RANKL. We also evaluated the effect of direct activation of NOD2 receptor on osteoclastogenesis, by the activation of this receptor in preosteoclasts culture, with different concentrations of muramyl dipeptide. The results show no difference in the number of TRAP-positive cells. Although it did not alter the osteoclasts differentiation, the activation of NOD2 receptor led to a significant increase of cathepsin K expression. We confirm that this enzyme was active, since the osteoclasts resorption capacity was enhanced by muramyl dipeptide stimulation, evaluated in osteoassay plate. These results show that the lack of NOD2 receptor impairs the bone resorption, suggesting that NOD2 receptor could contribute to the progression of bone resorption in experimental model of periodontitis. The stimulation of NOD2 by its agonist, muramyl dipeptide, did not affect osteoclastogenesis, but it does favor the bone resorption capacity identified by increased osteoclast activity.